34th Aerospace Sciences Meeting and Exhibit 1996
DOI: 10.2514/6.1996-643
|View full text |Cite
|
Sign up to set email alerts
|

Screech tones from rectangular jets with spanwise oblique shock-cell structures

Abstract: Understanding screech is especially important for the design of advanced aircraft because screech can cause sonic fatigue failure of aircraft structures. Although the connection between shock-cell spacing and screech frequency is well understood, the relation between nonuniformities in the shock-cell structures and the resulting amplitude, mode, and steadiness of screech have remained unexplored. This paper addresses the above Issues by intentionally producing spanwise (larger nozzle dimension) variations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 20 publications
2
53
0
Order By: Relevance
“…According to the stability theory, the description of the instability wave in space and 45 time can be decomposed into a product of terms corresponding to the shear-layernormal variation (the eigenfunction), the streamwise growth, and the streamwise convection:…”
Section: Inflow Forcingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the stability theory, the description of the instability wave in space and 45 time can be decomposed into a product of terms corresponding to the shear-layernormal variation (the eigenfunction), the streamwise growth, and the streamwise convection:…”
Section: Inflow Forcingmentioning
confidence: 99%
“…The twin jet configuration has been studied [49,50,55] and has been shown to result in screech of increased intensity. The effects of unusual nozzle geometry on screech have been studied by several [29,34,45,72,75], including beveled, elliptical, and triangular nozzle geometries.…”
mentioning
confidence: 99%
“…Figure 1.34 shows a comparison of the numerical results of (1.51) and the experimental measurements of Raman (1996). There is excellent agreement between predictions and measurements over the Mach number range of 1.1 < M j < 1.8.…”
Section: Fundamental Screech Tone Frequencymentioning
confidence: 77%
“…Screech tones, relating to jet noise generation, may also have a detrimental effect on aircraft structures. Raman [14] showed that the level of screech tones altered depending on a span-wise nozzle exit geometry. Rectangular jets have also been used for combustors [15,16] and they lead to enhancement of the combustion performance due to axis switching associated with self-induced vortex ring deformations.…”
Section: Introductionmentioning
confidence: 99%